2021
DOI: 10.3389/fimmu.2020.599974
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of the Membrane Attack Complex in Healthy and Diseased Human Kidneys

Abstract: The membrane attack complex—also known as C5b-9—is the end-product of the classical, lectin, and alternative complement pathways. It is thought to play an important role in the pathogenesis of various kidney diseases by causing cellular injury and tissue inflammation, resulting in sclerosis and fibrosis. These deleterious effects are, consequently, targeted in the development of novel therapies that inhibit the formation of C5b-9, such as eculizumab. To clarify how C5b-9 contributes to kidney disease and to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 212 publications
4
44
0
1
Order By: Relevance
“…More pronounced C5b-9 staining is often seen in proteinuria (56), however, which is in accordance with our immunohistochemical observations. Earlier studies have also reported apical staining in proteinuria but tended to regard this as an unspecific signal related to proteinuria (56). In rats with nephrotic range proteinuria, deposition of C5b-9 was predominantly apical, and inhibition of membrane attack complex formation was therapeutic (59).…”
Section: Discussionsupporting
confidence: 93%
“…More pronounced C5b-9 staining is often seen in proteinuria (56), however, which is in accordance with our immunohistochemical observations. Earlier studies have also reported apical staining in proteinuria but tended to regard this as an unspecific signal related to proteinuria (56). In rats with nephrotic range proteinuria, deposition of C5b-9 was predominantly apical, and inhibition of membrane attack complex formation was therapeutic (59).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, terminal pathway components were associated with a higher histological score and lower kidney function. In accordance, multiple studies have found a relationship between C5b-9 staining in IgAN and histological lesions as well as clinical outcomes [ 120 ]. Overall, glomerular C5b-9 deposition in IgAN correlates with the extent of glomerulosclerosis, mesangial expansion, hypercellularity, interstitial inflammation, and fibrosis as well as tubular atrophy, whereas tubular C5b-9 staining is associated with the extent of tubular atrophy, interstitial inflammation, and interstitial fibrosis [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ].…”
Section: The Complement System In Iga Nephropathysupporting
confidence: 63%
“…However, decreased CR1 expression on podocytes is a shared histopathological feature among glomerular diseases and is not specific to IgAN [ 119 ]. In addition to the mesangium, C5b-9 can also be found along the capillary wall in the glomerulus, Bowman’s capsule, the tubular basement membrane, and the vascular wall [ 120 ]. In recent studies, the presence of C5b-9 in IgAN biopsies has been confirmed by proteomics analysis of microdissected glomeruli [ 96 ].…”
Section: The Complement System In Iga Nephropathymentioning
confidence: 99%
“…Deposited Gd-IgA1-auto-Ab immune complexes activate the alternative and lectin pathways but not the classical pathway in IgAN [7]. For instance, C3, properdin, complement factor H, C5b-9 of the alternative pathway, and C4d (the mannose-binding lectin of the lectin pathway) are present in the mesangial immune deposits in kidney tissue from patients with IgAN [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…All three complement pathways lead to C5 convertase production, which cleaves into C5a and C5b. C5b binds to C6, C7, C8, and C9, producing C5b-9 [7]. C5b-9, also known as the membrane attack complex, is the end-product of the three complement pathways via this terminal complement cascade [11].…”
Section: Introductionmentioning
confidence: 99%